2019
DOI: 10.4103/aja.aja_105_18
|View full text |Cite
|
Sign up to set email alerts
|

The effect of vitamin D on sperm motility and the underlying mechanism

Abstract: Vitamin D deficiency is a common health issue around the world. We therefore evaluated the associations of semen quality with both serum and seminal plasma vitamin D levels and studied the mechanisms underlying these by incubating spermatozoa with 1,25(OH) 2 D in vitro . Two hundred and twenty-two men were included in our study. Vitamin D was detected using an electrochemiluminescence method. Spermatozoa used for in vitro experiments were iso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
16
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(17 citation statements)
references
References 58 publications
1
16
0
Order By: Relevance
“…Indeed, vitamin D was reported to be unrelated [62,89,90,[92][93][94] or positively associated to sperm count [62,78,87,88,91,95]. Most of the studies showed that circulating levels of 25-hydroxy-vitamin D3 were not associated with sperm morphology [61,62,78,89,[93][94][95][96]. Only four studies showed a positive association [66,87,88,90].…”
Section: ) Effects On Seminal Parameters In Humansmentioning
confidence: 99%
See 1 more Smart Citation
“…Indeed, vitamin D was reported to be unrelated [62,89,90,[92][93][94] or positively associated to sperm count [62,78,87,88,91,95]. Most of the studies showed that circulating levels of 25-hydroxy-vitamin D3 were not associated with sperm morphology [61,62,78,89,[93][94][95][96]. Only four studies showed a positive association [66,87,88,90].…”
Section: ) Effects On Seminal Parameters In Humansmentioning
confidence: 99%
“…One more recent in vitro study explored the relationships between both serum and seminal plasma vitamin D levels and semen quality, by incubating spermato-zoa with 1,25(OH)2 vitamin D. In vitro, sperm kinetic parameters increased after incubation for 30 minutes with 1,25(OH)2 vitamin D. The upward migration of spermatozoa increased remarkably with increasing adenosine triphosphate concentration, showing a positive correlation between seminal plasma vitamin D and sperm kinetics. In this context, seminal plasma vitamin D may better reflect the status of male reproduction [95].…”
Section: ) Effects On Seminal Parameters In Humansmentioning
confidence: 99%
“…In addition, it causes incomplete spermatogenesis and degenerative changes as well (Ramlau-Hansen et al, 2011). Some studies have shown that the serum and seminal plasma vitamin D may be involved in regulating sperm quality (morphology, concentration, motility and acrosome reaction) (Aquila et al, 2009;Ramlau-Hansen et al, 2011;Blomberg Jensen et al, 2011;Jueraitetibaike et al, 2019), and others showed that vitamin D has anti-apoptosis function in some cells (Zhang et al, 2007); therefore, the authors decided to assess the role of this vitamin in apoptosis and sperm quality in asthenozoospermic and healthy men. For this purpose, we used VD under in vitro condition like ART and evaluated sperm quality (morphology, motility, chromatin integrity) and apoptosis using Annexin V and TENNEL.…”
Section: Introductionmentioning
confidence: 99%
“…The ATP Assay Kit (Beyotime) was used to determine the ATP content in boar sperm samples on day 0 and the 3rd and 7th days of the experiment (Jueraitetibaike et al, 2019). Briefly, the lysis buffer was added to the sample to extract intracellular ATP from boar sperm.…”
Section: Determination Of Atp Content δψM and Gapdh Activitymentioning
confidence: 99%